2017
DOI: 10.1590/0103-8478cr20160553
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence of early vertical transmission of Leishmania ( Leishmania ) infantum in a dog

Abstract: Visceral leishmaniasis (VL) is caused by the protozoon Leishmania infantum. Transmission of this parasite to hosts occurs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
2
0
4
Order By: Relevance
“…Additional information to support the proposal of tolerance development by congenital infection is that Leishmania parasites were identified colonizing the thymus of a girl born to a mother with VL infection, who died at 7 months of age due to VL . Furthermore, in other studies, parasites were identified in the thymus of a newborn dog, as well as in a dog embryo at the end of the first trimester . Thus, in these cases, peptides from Leishmania antigens were potentially present on the surface of DCs in the thymus during the T‐cell–negative selection period.…”
Section: Effect Of Leishmania Infection During Pregnancy On the Immunmentioning
confidence: 77%
“…Additional information to support the proposal of tolerance development by congenital infection is that Leishmania parasites were identified colonizing the thymus of a girl born to a mother with VL infection, who died at 7 months of age due to VL . Furthermore, in other studies, parasites were identified in the thymus of a newborn dog, as well as in a dog embryo at the end of the first trimester . Thus, in these cases, peptides from Leishmania antigens were potentially present on the surface of DCs in the thymus during the T‐cell–negative selection period.…”
Section: Effect Of Leishmania Infection During Pregnancy On the Immunmentioning
confidence: 77%
“…In particular, infection of the canine reproductive tract has received substantial attention since venereal and vertical transmission were reported (PANGRAZIO et al, 2009;SILVA et al, 2009). Early vertical transmission to the embryo in a pregnant dog infected with L. infantum was detected by molecular means (OLIVEIRA et al, 2017). In the United States, where vectorial transmission L. infantum has not been proven, cases of vertical transmission in dogs appear to be important for the maintenance of the parasite circulation in the population (BOGGIATTO et al, 2011;TOEPP et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A leishmaniose visceral (LV) é responsável por alterações em órgãos como o fígado, baço e a medula óssea, e tem como principais patógenos no Velho Mundo as espécies Leishmania donovani e Leishmania infantum (AKHOUNDI et al, 2016). No Novo Mundo o agente é da espécie L. infantum (sinônimo de L. chagasi), com predomínio da forma zoonótica de transmissão na qual o cão é o principal reservatório e desenvolve a doença leishmaniose visceral canina (LVC) (MENDONÇA et al, 2017;OLIVEIRA et al, 2017).…”
Section: Introductionunclassified
“…A transmissão da leishmaniose ocorre por flebótomos do gênero Lutzomya e Phlebotomus (MAIA; CAMPINO, 2008;OLIVEIRA et al, 2015), fêmeas, que necessitam de alimentação por sangue para maturação dos ovos. O inseto contaminado transmite o parasita durante o repasto sanguíneo e tem maior atividade pela manhã e ao anoitecer (OLIVEIRA et al, 2017).…”
Section: Introductionunclassified
See 1 more Smart Citation